Understanding Listeria biofilms: formation, ecology, and control in the produce industry - Deniz, Aysu (My University, 2025)
Listeria monocytogenes, a major foodborne pathogen, has been a growing concern in the fresh produce industry and is increasingly recognized as a vehicle for transmission of foodborne illnesses. Its persistence and contamination potential are strongly associated with its ability to form biofilms. Hard-to-clean sites in food processing environments can provide favorable conditions for biofilm establishment and survival. Exposure of these biofilms to sublethal concentrations of sanitizers can trigger stress response mechanisms, leading to alterations in gene expression that promote adaptive response. Beyond single-species systems, a further challenge is the frequent occurrence of L. monocytogenes in multispecies biofilms, particularly with Pseudomonas spp., a common spoilage microorganism. These mixed communities exhibit enhanced resistance and tolerance to sanitizing practices, creating greater challenges for effective control. Therefore, the main objectives of this study were to: 1) Assess the growth of L. monocytogenes biofilms on common food processing surfaces used in the fresh produce industry and evaluate the efficacy of commercially available sanitizers alone or simultaneously with UV-C light; 2) Characterize the transcriptional response of L. monocytogenes biofilms exposed to sublethal concentrations of commercial sanitizers and identify mechanisms involved in biofilm adaptation; and 3) Investigate the interactions between Pseudomonas fluorescens and L. monocytogenes in dual-species biofilms and evaluate the efficacy of commercially available sanitizers against these biofilms across different food-contact surfaces. Multi-strain L. monocytogenes biofilms were grown in a Centers for Disease Control and Prevention (CDC) biofilm reactor on stainless steel, nylon, polyvinyl chloride (PVC), high density polyethylene (HDPE), and Teflon® for up to 96 h. Mature biofilms were exposed to 120 ppm peracetic acid (PAA), silver dihydrogen citrate (SDC; 4.85% citric acid and 0.003% silver ions), 4% lactic acid, and UV-C light (254 nm) for 1 or 5 min by spraying. Biofilm architecture was evaluated using Laser Scanning Confocal Microscopy (LSCM) before and after treatments. Uninoculated surface materials showed different topographical characteristics and when mature biofilms were treated for 1 min with different sanitizers, biomass was visibly affected. Antimicrobial treatment and the interaction of treatment and material showed significant effects (P < 0.05). All tested liquid sanitizers significantly reduced biofilm cell populations as compared to controls (P < 0.05), with PAA and lactic acid demonstrating the highest efficacy across surfaces. However, simultaneous application of UV-C light with sanitizers did not statistically improve treatment efficacy. Given the observed variation in sanitizer efficacy against L. monocytogenes biofilms populations observed, transcriptomic analysis was conducted to further explore the relationship between sanitizer-induced stress and gene expression. Biofilms were exposed to sublethal concentrations of PAA (10 ppm), chlorine (10 ppm), SDC (4.85% citric acid and 0.003% silver ions), and lactic acid (0.4%), with untreated biofilms serving as controls. L. monocytogenes biofilms responded differently to sublethal stresses of these sanitizers. Among them, chlorine and peracetic acid induced the most rapid and significant transcriptional changes. Comparative analysis of differentially expressed genes (DEGs) revealed both unique and shared transcriptional responses across treatments. Chlorine induced the highest number of unique upregulated genes, while chlorine and PAA shared a subset of commonly regulated genes. This suggested both distinct and overlapping stress response mechanisms depending on the sanitizer used. Chlorine exposure triggered regulatory and transport systems, while PAA induced ion transport and ABC transporters. These sanitizer-specific responses suggested distinct adaptive strategies that may contribute to persistence. Since complex interspecies interactions can enhance resistance and tolerance to sanitation efforts, this study also evaluated the efficacy of commercial sanitizers against dual-species biofilms of L. monocytogenes and P. fluorescens. Biofilm production capacities of these species were first assessed by crystal violet staining. Dual-species biofilms were then grown in a CDC biofilm reactor on stainless steel, PVC, Teflon, and HDPE surfaces at 22 ± 2°C for 96 h. Mature biofilms were treated by immersion with the previously tested sanitizers, along with chlorine (500 ppm) for 5 min. Surviving cells were recovered on selective and general media. In addition, growth dynamics of both species were monitored over time, and LSCM was used to visualize colonization patterns and spatial organization within the biofilms. Results revealed that both P. fluorescens and L. monocytogenes were found to be biofilm formers with different production capacities and P. fluorescens showed significantly higher biomass production than L. monocytogenes (P < 0.05). Material, treatment, and their interaction had significant effects on microbial recovery (P < 0.05). Among sanitizers tested, chlorine was the most effective showing enhanced effectiveness on stainless steel where the total counts were reduced from 8.43 ± 0.32 log CFU/coupon to 5.26 ± 0.09 log CFU/coupon. A similar trend was observed when L. monocytogenes and P. fluorescens populations were enumerated individually. PAA was also effective against dual-species biofilms. On HDPE, PAA treatment resulted in the combined counts of 6.27 ± 0.15 log CFU/coupon where untreated control was 8.63 ± 0.34 log CFU/coupon. Overall, this study demonstrates that L. monocytogenes biofilms exhibit sanitizer and surface dependent responses and provides insight into how interspecies interactions and sanitizer adaptations affect their persistence on food processing surfaces. These findings provide insightful information on the use of a combined sanitizing approaches and support the development of more effective strategies for controlling biofilms on food processing surfaces in the fresh produce industry.
Keywords: Listeria; Biofilm; Sanitizer; Pseudomonas; Transcriptomics